ANALISIS PENGGUNAAN KANDOUSHI DALAM TINDAK TUTUR PADA KOMIK GEKKAN SHOUJO NOZAKI-KUN VOLUME 5 DAN 6 KARYA IZUMI TSUBAKI - Pachira Desi Dariasri; Yuni Masrokhah; Ana Natalia (Prosiding Seminar Nasional Berseri, 2020)
Kandoushi is a word that expresses a speaker's feelings in speech act. Kandoushi is an expression of the speaker's feelings without changing the meaning of the sentence in speech act. The purpose of this research was to determine the type of Kandoushi, how the meaning and use of Kandoushi in speech acts contained in the comic Gekkan Shoujo Nozaki-kun by Izumi Tsubaki. This research uses descriptive method with a qualitative approach. The data collection technique used in this research is literature study techniques, then using the matching technique as data analysis. The object of this research study is the comic Gekkan Shoujo Nozaki-kun. As a result of the 50 data found, Kandoushi was divided into four types: kandou, yobibake, ootto, aisatsugo. Besides that, the meaning of Kandoushi is divided based on the type of Kandoushi, the type of Kandou which is surprised, wonder, annoyed, amazed, strange, worried, and understanding, Yobibake is a call, calling, invite, and appeal, Ootto is to agree, disagree, rejection, understanding, and Responses, and Aisatsugo namely separation, thanks and greetings. Then, the use of Kandoushi there are 3 types of usage in speech acts namely Locution, Illocution, and Perlocution.